Grozovye gody. Vospominanija starych kommunistov. [Red.-sost. I.N. Kirillov, A.M. Tarasenko. S učast. M. Frunze, P. Postyševa, S. Balašova i dr.] (Kn. izd., 1961)
Partijnyj archiv Ivanovskogo obkoma KPSS.